1, 2, 4-thiadiazol-5(4H)-ones: a new class of selective inhibitors of Trypanosoma cruzi triosephosphate isomerase. Study of the mechanism of inhibition. (1st October 2013) - Alvarez, Guzmán; Aguirre-López, Beatriz; Cabrera, Nallely; Marins, Eliã B.; Tinoco, Luzineide; Batthyány, Carlos Ignacio; de Gómez-Puyou, Marieta Tuena; Puyou, Armando Gómez; Pérez-Montfort, Ruy; Cerecetto, Hugo; González, Mercedes
Abstract : Context : Triosephosphate isomerase (TIM) is a ubiquitous enzyme that has been targeted for the discovery of small molecular weight compounds with potential use against Trypanosoma cruzi, the causative agent of Chagas disease. We have identified a new selective inhibitor chemotype of TIM from T. cruzi ( Tc TIM), 1, 2, 4-thiadiazol-5(4 H )-one. Objective : Study the mechanism of Tc TIM inhibition by a 1, 2, 4-thiadiazol derivative. Methods : We performed the biochemical characterization of the interaction of the 1, 2, 4-thiadiazol derivative with the wild-type and mutant Tc TIMs, using DOSY-NMR and MS experiments. Studies of T. cruzi growth inhibition were additionally carried out. Results and conclusion : At low micromolar concentrations, the compound induces highly selective irreversible inactivation of Tc TIM through non-covalent binding. Our studies indicate that it interferes with the association of the two monomers of the dimeric enzyme. We also show that it inhibits T. cruzi growth in culture.